Peningkatan Hasil Belajar Ilmu Pengetahuan Sosial (IPS) Melalui Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) Pada Murid Kelas V SD Inpres Borong Jambu II Kota Makassar - Nur Afni; Abdul Wahid; Abrina Maulidnawati Jumrah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
The objective of this research is to determine the improvement of learning outcomes in Social Sciences (IPS) by using the Cooperative Learning Model Type Student Teams Achievement Division (STAD) for fifth grade students in SD Inpres Borong Jambu II Makassar City. This research is a descriptive study designed through class action research (class room action research). This classroom action research was conducted in two cycles, each cycle carried out 4 meetings. This research was conducted for fifth grade students in SD Inpres Borong Jambu II Makassar City, with 10 students. A total of 5 men and 5 women. The research instruments were tests and observation sheets. Data were analyzed quantitatively and qualitatively. The results achieved quantitatively are: (1) In the first cycle, the average value of learning outcomes is obtained  fifth grade students in SD Inpres Borong Jambu II Makassar City, namely 63.5 (2) In the second cycle the average value of learning outcomes fifth grade students in SD Inpres Borong Jambu II Makassar City is higher, reaching 85, so it can be concluded that the increase is 21.5. Especially in changing attitudes, motivation, enthusiasm, and student learning outcomes in understanding the material.